TINDAK PIDANA INSIDER TRADING DALAM REGULASI INDONESIA - Daniel Bastian (2023)
Insider trading is an act carried out by insiders to engage in securities transactions based on non-public information possessed by insiders for personal gain. This act undermines the integrity of the capital market. Indonesia prohibits insider trading based on positive legal provisions stated in Article 95, Article 96, and Article 98 of Law No. 8 of 1995, as well as Article 22 of Law No. 4 of 2023, which amends Article 97 of Law No. 8 of 1995. This research is a normative study that uses a legal approach, case approach, and conceptual approach. Data collection is done through literature review, and secondary data is analyzed using primary, secondary, and tertiary legal materials. The data analysis technique used is a qualitative descriptive approach. The aim of this research is to determine the criminal liability of perpetrators of insider trading and the enforcement of criminal law against them. The forms of criminal liability for perpetrators of insider trading are imprisonment and fines. The enforcement of the law against perpetrators of insider trading is carried out through repressive measures through criminal proceedings. The law enforcement against insider trading has not yet introduced preventive measures to prevent such crimes. The law enforcement against insider trading in Indonesia, conducted by law enforcement agencies, appears to be passive, and it is necessary for the OJK to optimize law enforcement through the use of technology.